The worldwide impact of urbanisation on avian functional diversity - Daniel Sol; Christopher Trisos; Cesc Múrria; Alienor Jeliazkov; Cesar González‐Lagos; Alex L. Pigot; Carlo Ricotta; Christopher M. Swan; Joseph A. Tobias; Sandrine Pavoine (Ecology Letters, 2020)
Urbanisation is driving rapid declines in species richness and abundance worldwide, but the general implications for ecosystem function and services remain poorly understood. Here, we integrate global data on bird communities with comprehensive information on traits associated with ecological processes to show that assemblages in highly urbanised environments have substantially different functional composition and 20% less functional diversity on average than surrounding natural habitats. These changes occur without significant decreases in functional dissimilarity between species; instead, they are caused by a decrease in species richness and abundance evenness, leading to declines in functional redundancy. The reconfiguration and decline of native functional diversity in cities are not compensated by the presence of exotic species but are less severe under moderate levels of urbanisation. Thus, urbanisation has substantial negative impacts on functional diversity, potentially resulting in impaired provision of ecosystem services, but these impacts can be reduced by less intensive urbanisation practices.